2018
DOI: 10.1177/0040517518803779
|View full text |Cite
|
Sign up to set email alerts
|

Modeling for predicting the thermal protective and thermo-physiological comfort performance of fabrics used in firefighters' clothing

Abstract: Standardized test methods are available for measuring the thermal protective as well as thermo-physiological comfort Performance of fabrics used in firefighters' clothing. However, these tests are usually fabric destructive in nature, time consuming, and/or expensive to carry out on a regular basis. Hence, the availability of empirical models could be useful for conveniently predicting the thermal protective and thermo-physiological comfort performances from the fabric properties. The aim of this study is to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 25 publications
(29 reference statements)
2
40
0
Order By: Relevance
“…Recently, Mandal et al (2019) [ 61 ] evaluated the thermo-physiological comfort performance of wide range of fabrics used in workwear. In this study, ISO 18640-1:2018 and ISO 18640-2:2018 standards were used to evaluate the thermo-physiological comfort performance of fabrics in terms of time required to generate heat stress on wearers’ bodies.…”
Section: Characterization and Modeling Of Thermo-physiological Comfort Performance Of Polymeric Textile Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Mandal et al (2019) [ 61 ] evaluated the thermo-physiological comfort performance of wide range of fabrics used in workwear. In this study, ISO 18640-1:2018 and ISO 18640-2:2018 standards were used to evaluate the thermo-physiological comfort performance of fabrics in terms of time required to generate heat stress on wearers’ bodies.…”
Section: Characterization and Modeling Of Thermo-physiological Comfort Performance Of Polymeric Textile Materialsmentioning
confidence: 99%
“…In this study, it has been found that fabric weight, water spreading speed, and evaporative resistance are the significant properties to affect the thermo-physiological comfort performance of fabrics. By using these properties, Mandal et al (2019) [ 61 ] also developed the MLR and ANN models for predicting the thermo-physiological comfort performance of fabrics; it has been found that ANN model could perform better for predicting the thermo-physiological comfort performance of fabrics.…”
Section: Characterization and Modeling Of Thermo-physiological Comfort Performance Of Polymeric Textile Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is becoming more demanding, complex and difficult to achieve certain material properties, prescribed by standards for a particular purpose, and it is even more difficult to achieve the sustainability during use. Therefore, finishing processes (surface treatments and layering) are conducted on the material, which simultaneously affect the property of breathability, resulting in the insufficient material comfort [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%